Pilar Ekonomi Islami: Rekonstruksi Aktivitas Ekonomi Berdasarkan Al-Qur’an dan Hadis - Aisyah Aisyah; Risma Risma; Saiful Muchlis; Rika Dwi Ayu Parmitasari (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2025)
This study aims to explore the Islamic legal foundations (shar‘i) of economic activities based on the Qur'an and the Hadith. Islam, as a comprehensive religion, governs all aspects of life, including economics, emphasizing spiritual values, ethics, and justice. Utilizing a qualitative approach through literature review, this research identifies core concepts of Islamic economics such as production, distribution, and consumption, all grounded in the principles of monotheism (tawhid), human responsibility as stewards (khalifah), and justice. The study further examines the application of key principles such as public interest (maslahah), mutual consent (ridha), blessing (barakah), and transparency in economic transactions, as well as prohibitions on usury (riba), uncertainty (gharar), gambling (maysir), hoarding (ihtikar), and trade of unlawful goods. The findings demonstrate that Islamic economic activity is not merely a worldly necessity but also a form of worship aimed at achieving. By adhering to these shar‘i principles, Islamic economics offers a just, sustainable, and welfare-oriented system for society as a whole.